2015
DOI: 10.3389/fmicb.2015.00673
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the avian gut microbiota: current trends and future directions

Abstract: Birds represent a diverse and evolutionarily successful lineage, occupying a wide range of niches throughout the world. Like all vertebrates, avians harbor diverse communities of microorganisms within their guts, which collectively fulfill crucial roles in providing the host with nutrition and protection from pathogens. Across the field of avian microbiology knowledge is extremely uneven, with several species accounting for an overwhelming majority of all microbiological investigations. These include agricultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
193
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(227 citation statements)
references
References 132 publications
28
193
6
Order By: Relevance
“…The phylum-level results of our characterization of junco microbiota were consistent with studies of avian microbiota in general: they were typified by Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes (Hird et al, 2014;Waite and Taylor, 2015). More specifically, our genus-level data agreed with a recent cultivation-based survey of junco ventral feather bacteria, which included Proteobacteria (Brevundimonas, Methylobacterium, Pseudomonas, Rhizobium, and Sphingomonas) and Firmicutes (Staphylococcus) that were widespread and abundant in our dataset (Supplemental Data 1) (Dille et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The phylum-level results of our characterization of junco microbiota were consistent with studies of avian microbiota in general: they were typified by Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes (Hird et al, 2014;Waite and Taylor, 2015). More specifically, our genus-level data agreed with a recent cultivation-based survey of junco ventral feather bacteria, which included Proteobacteria (Brevundimonas, Methylobacterium, Pseudomonas, Rhizobium, and Sphingomonas) and Firmicutes (Staphylococcus) that were widespread and abundant in our dataset (Supplemental Data 1) (Dille et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study add to a growing body of literature indicating that environments, including social environments, can have pronounced effects on avian cloacal and uropygial gland microbiota (Waite and Taylor, 2015). For example, in free-living barn swallows mated pairs share similarities in their cloacal microbiota (Kreisinger et al, 2015), and experiments with wild kittiwakes, Rissa tridactyla, and captive zebra finches have demonstrated that symbiotic bacteria are readily transmitted between the cloacae of mated pairs (Kulkarni and Heeb, 2007).…”
Section: Effects Of Social Environment and Genetic Relatednesssupporting
confidence: 53%
“…Proteobacteria and Firmicutes are common in the gastrointestinal trait of birds (Godoy-Vitorino et al 2012;Waite et al 2012;Waite & Taylor 2015). A more detailed description of the bacterial community at a lower taxonomic level showed that the most abundant genera differed from those observed in previous studies: the genera Ralstonia, Pseudomonas, Aeribacillus, and Arenimonas were abundant in our samples, while they were not found in the two previous studies in the Czech Republic (Kreisinger et al 2015(Kreisinger et al , 2017.…”
Section: Discussioncontrasting
confidence: 86%
“…The observed low overlapping of barn swallow CMs is consistent with the hypothesis that environmental features of the areas where individuals live are the main drivers of avian microbiota diversification and that CMs may therefore largely differ among geographical populations of the same species (Lucas & Heeb 2005;Waite & Taylor 2015). This confirms the importance of studies describing the microbiota of different and distant geographical populations of the same species.…”
Section: Discussionsupporting
confidence: 86%
“…, and that the bacterial load in the GI tract is higher than airways 27,28 , avian strains may be adapted to the high concentrations of LPS that they encounter inside the host and in feces.…”
mentioning
confidence: 99%